La 17e nuit d’at-Tawḥīdī - Guillaume de Vaulx d’Arcy (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: At-Tawḥīdī’s 17th Night : Refutation of a Threatening Heresy, i.e. the Epistles of the Brethren in Purity. The 17th night of the Kitāb al-imtāʿ wa-l-muʾānasa written by Abū Ḥayyān at-Tawḥīdī can no longer be considered as a testimony on the authorship of the Rasāʾil Ikhwān aṣ-ṣafā, for the very epistles were already written around 307/920. Indeed, they were well-known in Andalusia in the West around the middle of the century, and among the Ismāʿīlīs in the East already at its beginning. Furthermore, we can demonstrate that their doctrine would be anachronistic out of the late third/ninth century. Then, the 17th night must be reinterpreted as the rebuttal of the Brethren in Purity’s views in a very structured manner employing different characters : the minister Ibn Saʿdān, al-Bukhārī, Zayd b. al-Rifāʿa, al-Maqdīsī, an-Nīsābūrī and al-Balkhī, in order to represent the different degrees of initiation and symbolize progression of the heresy.